Removal of perfluoroalkyl acids and common drinking water contaminants by weak-base anion exchange resins: Impacts of solution pH and resin properties. (1st December 2022) - Kassar, Christian; Graham, Cole; Boyer, Treavor H.
Highlights: Weak-base (WB) and strong-base (SB) anion exchange resins (AERs) studied for pH. At acidic and neutral pH, similar contaminant removal by WB and SB AERs. Contaminant selectivity of WB AER due to polymer composition. Electrostatic interactions are diminished for WB AER at alkaline pH. Aqueous alkaline solution has great potential for regeneration of WB AER. Abstract: The underlying chemistry of weak-base (WB) anion exchange resins (AERs) for contaminant removal from water is not well documented in the literature. To address this, batch adsorption experiments were conducted at pH 4, 7, and 10 using two representative WB-AERs (polyacrylic IRA67 and polystyrene IRA96) and two representative strong-base (SB) AERs (polyacrylic IRA458 and polystyrene A520E), of differing polymer composition, for the removal of nitrate, sulfate, 3-phenylpropionic acid (3-PPA) as surrogate for natural organic matter, and six perfluoroalkyl acids (PFAAs). Under acidic (pH 4) and neutral (pH 7) conditions, the selectivity of AERs for each contaminant was predominantly influenced by polymer composition followed by the size of the resin functional group. This result reflected the WB-AERs being fully protonated and functioning identical to SB-AERs. Isotherm model parameters revealed WB-AER had higher capacity than SB-AER with analogous polymer composition and porosity regardless of resin selectivity for each contaminant. Under basic conditions (≥ pH 10), contaminant removal by WB-AERs declined due to deprotonation of the tertiary amine functional groups. Removal of PFAAs by the more hydrophobic polystyrene WB-AER (IRA96) remained approximately constant with changing pH, which was possibly due to electrostatic interactions with remaining protonated amine functional groups on the resin.